“Kejutan! Hadiah Ulang Tahun dari Brand”: Strategi Membangun Cinta atau Gimmick Semata? - Kinanti, Mutiara; Daulay, Muhammad Yasser Iqbal (STIE Indonesia Banking School, 2025)
Birthdays are special moments that many people look forward to. Birthday celebrations are often held in different ways and styles, ranging from private celebrations to lavish parties. The purpose of this study was to determine the direct effect of brand relationship quality influenced by brand warmth and brand intimacy as mediating variables to generate brand love through birthday treats. This research uses a quantitative approach with a survey method where data was collected using a Likert scale-based questionnaire based on relevant literature. Respondents in this study were consumers who received birthday gifts from brands, and the sample size was determined Structural Equation Modeling (SEM) was used to conduct data analysis to test the relationship between variables. According to this study, brand relationship quality (BRQ) plays an important positive and significant role in brand love. This influence is realized both directly and through the mediation of brand warmth and brand intimacy. This study makes a theoretical contribution by enhancing our understanding of the emotional mechanisms that link consumer and brand experiences. Practically, these findings can help marketers develop a strategy of